Painting: Documents of Contemporary Art. - Meyers, Terry, R.; Art & Language; Bryson, Norman; Crimp, Douglas; Daniel, Birnbaum; Deleuze, Gilles; Egenhofer, Sebastian; Foster, Hal; Gilbert-Rolfe, Jeremy; Graw, Isabelle; Groos, Ulrike; Halle, Howard; et al. (London : Whitechapel Gallery, 2011)
Francis Alÿs, Kevin Appel ; Glenn Brown ; Pavel Büchler ; Daniel Buren ; Ingrid calame ; Vija Celmins ; John Currin ; Atul Dodiya ; Marlene Dumas ; Olafur Eliasson ; Bernard Frize ; Katharina Grosse ; Andreas Gursky ; Wade Guyton ; Peter Halley ; Mary Heilmann ; Gary Hume ; Vanessa Jackson ; Martin Kippenberger ; Jutta Koether ; Michael Krebber ; Jonathan Lasker ; Paul Mc Carthy ; Suzanne McCelland ; Beatriz Milhazes ; Marilyn Minter ; Takashi Murakami ; Surendran Nair ; Tam Ochiai ; Albert Oehlen ; Lari Pittman ; Sigmar Polke ; Monique Prieto ; Gerhard Richter ; Robert Ryman ; David Salle ; Cgéri Samba ; Juliao Sarmento ; Jim Shaw ; Jessica Stockholder ; Hiroshi Sugito ; Philip Taaffe ; Luc Tuymans ; Jef Wall ; Sue Williams
schilderkunst van de 21ste eeuw, verschillende thema's, discussie moderne/ postmoderne schilderkunst
boek